Pengaruh Ekspektasi Konsumen, Nilai Konsumen Dan Kepuasan Konsumen Terhadap Loyalitas Konsumen - ., Sujana; Pandu, Maudrey (Jurnal Ilmiah Manajemen Kesatuan, 2018)
The purpose of this research isto find out how the influence of customers expectation, customers value, and customers satisfaction on customers loyalty.Thevariables of expectations, value, satisfaction and loyalty of the customers will then be associated and calculated to obtain robustness of the influence. The results of the study showed that value obtained table standardized coefficients beta x1 (expectations of y (loyalty consumers) of 0,038 .X2 (a value of y (loyaltyconsumers) of 0,188 .X3 (satisfaction of y (loyalty consumers) of 0,028. The evaluation resulted from the calculation is that customers loyalty can beinfluenced by expectations, value and satisfaction of customers. The findings conclude that it is important for the marketing department to focus on developingand increasing the quality of their products and/or services to maintain a sustainable customers’ loyalty.